Fraud Triangle Perspective on The Tendency of Fraudulent Financial Statements in Non-financial State-Owned Enterprises - Nindya Saphira Maharani Rinaldo; Reni Oktavia; Yunia Amelia (Lighthouse Publishing, 2022)
Fraud is a problem that continues to exist in the organizational world. Fraud is difficult to eliminate but can be minimized by taking preventive measures by detecting things that have the potential to cause fraud. This study aims to analyze how the Fraud Triangle perspective detects the tendency of fraudulent financial statements with research samples of Non-financial State-Owned Enterprises listed on the IDX from 2016-2020. Fraudulent financial statements in this article were measured using Dechow F-Score and three dependent variables that represent each of the fraud triangle proxies with firm size as a control variable. Using logistic regression analysis, this research indicated pressure proxied by financial stability and measured using SALTA has a significant negative impact on the tendency of fraudulent financial statements. Opportunities proxied by the nature of industry and Rationalization proxied by changes in external auditors do not have a significant impact on the tendency of fraudulent financial statements.